Small Signal Analysis, Simulation and Experimental Validation of Non-Isolated Zeta Converter with Peak Current-Mode Control - Yilmaz, Abdurrahman; Garip, Muhammed (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2022)
In this study, we proposed a non-isolated Zeta converter (inverse SEPIC) and an experimental prototype was built and tested to verify the mathematical analysis results. Firstly, small signal analysis was presented with peak current-mode control. The PWM-switch model was utili-zed in Continuous Conduction Mode (CCM). The transfer function of output voltage was obtained including the equivalent series resistance (esr) of the output capacitor. Poles and zeros are given in symbolic form and proved their validity on a numerical example. Since the denomina-tor of the obtained yields of peak current-mode PWM switch model is a fifth order polynomial, approximate root analysis was used to find approximate poles and quality factors. The bode plots of proposed non-isolated Zeta converter was simulated with PSIM and compared with the Bode plots of the transfer function derived symbolically. The mathematical analysis was verified on an experimental prototype built and the results were in good agreement up to half the switching frequency.
Keywords: Zeta dc-dc converter; peak current-mode control; pwm-switch model; Engineering